Revised species definitions and nomenclature of the blue and purple/rose Cithaerias butterflies (Lepidoptera, Nymphalidae, Satyrinae) - Penz, Carla M. (Zootaxa, 2021)
This study reassesses the taxonomic status of Neotropical blue and purple/rose-colored Cithaerias butterflies, thus complementing a previous study of the rose-colored species. Based on comparative study of wing coloration and genitalia morphology, I revise species definitions and the taxonomic status of: Cithaerias andromeda, C. azurina STAT. REV., C. esmeralda STAT. REV., C. bandusia STAT. REV., C. pyropina, and C. songoana STAT. REV. Photographs of adults and illustrations of male and female genitalia are provided for all species. Of particular importance are the genitalia illustrations of male and female C. azurina, presented here for the first time, as well as finding a putative first female of Ecuadorean subspecies C. pyropina julia.